Going Hybrid or Full Online Learning? Lessons Learned from Middle School in Balikpapan - Warouw, Charlyne Sterly; Sihotang, Ronny Buha ((JELE) Journal Of English Language and Education, 2022)
This study aims to find out how satisfied the students are in learning during pandemic season more specific to whether going hybrid or full-online learning with teachersâ€™ performance as intervening variable. This research is Descriptive Quantitative where the primary data being collected from the answer of questionnaire responded by total of 388 respondents. This study covers middle schools in Balikpapan. Sampling data taken from grade 7, 8, and 9 junior high school. Descriptive analysis, t-test as partial test and path analysis being used to find exact numerical data by processing it on SPSS 26 version. The result of this study shows that the levels of full-online and hybrid teaching-learning, teacherâ€™s performance, and studentâ€™s learning satisfaction are in â€œgood levelâ€. The effect of full-online, hybrid learning significantly affecting teacherâ€™s performance, and full- online, hybrid learning, and teacherâ€™s performance partially affecting studentâ€™s learning satisfaction significantly. Path analysis for X1 to Z through Y shows that Total effect is greater than direct effect while indirect effect is smaller. Path analysis for X2 to Z through Y shows that total effect is greater than direct effect while indirect effect is smaller. This study is surely beneficial to the school where this study is conducted and also the educators by giving the overview about how the teaching-learning has impacted both teachers and students during this pandemic era. Itâ€™s also given opportunity to learn from, to improve technique in giving the best learning experiences to the studentsâ€™ satisfaction. The result of this study may show which is the best choice for the educational practice in the future